Endothelial Dysfunction in Obstructive Sleep Apnea - Budhiraja, Rohit (American Academy of Sleep Medicine, 2007)
Obstructive sleep apnea (OSA) is a common disorder and is associated with adverse cardiovascular consequences, including hypertension and coronary artery disease. While the mechanisms responsible for increased risk of cardiovascular events in OSA have not yet been fully elucidated, hypoxia, inflammation, obesity, metabolic dysregulation, and sympathetic activation, may contribute to these consequences. Endothelial dysfunction may be another link between OSA and cardiovascular disease. Dysfunctional endothelium is characterized by an imbalance in production of vasoactive hormones, increased adherence of inflammatory mediators to endothelial cells and hypercoagulability, and is a known risk factor for cardiovascular events. Studies have directly measured vascular endothelial function in patients with OSA and found a muted response compared to controls. Other studies have evaluated biochemical markers of endothelial function including circulating levels of vasoactive and thrombosis mediators and provide further proof of endothelial dysfunction in this disorder. A better appreciation of the role of the dysfunctional endothelium in OSA will help shed light on the pathogenesis of cardiovascular disease in this disorder and may lead to development of novel therapies aimed at preventing untoward outcomes. CITATION: Budhiraja R; Parthasarathy S; Quan SF. Endothelial dysfunction in obstructive sleep apnea. J Clin Sleep Med 2007;3(4):409-415.